Inhibition of GSK3β and RIP1K Attenuates Glial Scar Formation Induced by Ischemic Stroke via Reduction of Inflammatory Cytokine Production - Liu, Jin; Zhu, Yong-Ming; Guo, Yi; Lin, Liang; Wang, Zhan-Xiang; Gu, Feng; Dong, Xin-Yi; Zhou, Ming; Wang, Yi-Fan; Zhang, Hui-Ling (Frontiers in Pharmacology, 2020)
In the chronic phase following ischemic stroke, glial scars can prevent axonal regeneration and the intensification of inflammation. The protective effect of inhibition of glycogen synthase kinase-3β (GSK3β) or receptor-interacting protein 1 kinase (RIP1K) on ischemic stroke has been previously reported. The current study examined the effects of RIP1K and GSK3β on ischemic stroke-induced glial scar formation. To investigate this, we used an in vivo model of ischemic stroke based on middle cerebral artery occlusion for 90 min followed by reperfusion for 7 d, and an in vitro model in primary cultured astrocytes involving oxygen and glucose deprivation for 6 h followed by reoxygenation for 24 h. Both in vivo and in vitro, we found that SB216763, a GSK3β inhibitor, and necrostatin-1 (Nec-1), a RIP1K inhibitor, decreased levels of glial scar markers, including glial fibrillary acidic protein (GFAP), neurocan, and phosphacan. SB216763 and Nec-1 also decreased levels of inflammatory related cytokines, including interleukin-6 (IL-6), interleukin-1 β (IL-1β), and tumor necrosis factor-α (TNF-α). However, only Nec-1 increased the level of interleukin-1 receptor antagonist. Concurrent neutralization of TNF-α, IL-1β and IL-6 with their antibodies provided better reduction in OGD-induced increases in scar markers than obtained with separate use of each antibody. Further investigations showed that SB216763 reduced the levels of necroptosis-related proteins, including RIP1K, p-RIP1K, RIP3K, p-RIP3K, mixed lineage kinase domain-like protein (MLKL), and p-MLKL, while Nec-1 decreased the expression of p-GSK3β. Compared with Nec-1 (10 μM) and SB216763 (1 μM) alone, Nec-1 and SB216763 in combination reduced levels of GFAP, neurocan, and inflammatory-related cytokines. In conclusion, inhibition of GSK3β or RIP1K reduced glial scar formation induced by ischemic stroke. The underlying mechanisms might be related to the reduced expression of inflammatory-related cytokines and to the interference with interactions between GSK3β- and RIP1K-mediated pathways.